O realnih številih - Šemrl, Peter (Obzornik za matematiko in fiziko, 2008)
Most of secondary school pupils have a resonable intuitive understanding of real numbers. However, introducing reals in mathematical correct way is not easy task. Can we discuss these problems at the secondary school level?
Keywords: matematika; množice števil; realna števila